Development of an Integrated Biophysical Model to represent morphological and ecological processes in a changing deltaic and coastal ecosystem. (November 2018) - Baustian, Melissa M.; Meselhe, Ehab; Jung, Hoonshin; Sadid, Kazi; Duke-Sylvester, Scott M.; Visser, Jenneke M.; Allison, Mead A.; Moss, Leland C.; Ramatchandirane, Cyndhia; Sebastiaan van Maren, Dirk; Jeuken, Michelle; Bargu, Sibel
Abstract: Deltaic and coastal ecosystems are changing in response to natural and anthropogenic forces that require ecosystem-level restoration efforts to avoid habitat degradation or loss. Models that link ecosystem components of hydrodynamics, morphodynamics, nutrient and vegetation dynamics to represent essential processes and feedbacks are advancing the field of environmental modeling and are vital to inform coastal restoration decisions. An Integrated Biophysical Model was developed by creating a new vegetation dynamics component and linking it to other primary ecosystem components that included essential feedbacks. The model performance was evaluated by applying it to a deltaic ecosystem that included marshes and estuaries. The Integrated Biophysical Model output captured the general temporal and spatial environmental trends of key variables. This integrated model is capable to perform long-term simulations to assess responses of deltaic and coastal systems to global change scenarios and can be used to inform restoration strategies in ecosystems worldwide. Highlights: Development of Delft3D model to assess changing deltaic and coastal ecosystems. Hydrodynamics, morphodynamics, nutrient and vegetation dynamics were coupled. Integrated Biophysical Model captured the general environmental trends. Model is capable to run long-term simulations of environmental conditions. Software availability.